6x + 3 = 3 + 6x
0 = 0
many solutions
answer
infinitely many
Answer: No
Explanation:
According to factor theorem, if f(x)=0 then x is a factor of the given function or equation.
As x-1 is a factor
We equate x-1=0
x=1
Substituting in x^5-1, we have 1^5-1 =1-1=0.
Hence, it's a factor.
When coming to x^5+1, it would become 1^5+1=1+1=2
So x-1 isn't a factor of x^5+1.
Answer:
The answer is b because you are taking away from susan
Step-by-step explanation:
4 > x
step by step explanation:
13 > 3x + 1
-1 -1
12 > 3x
/3 /3
4 > x